Pertumbuhan dan Produksi Tiga Varietas Kedelai Hitam (glycine max (L.)Merril) Dengan Pemberian Berbagai Jenis Bahan Organik - Riza Syifani Nasution; Jonatan Ginting; Nini Rahmawati (Jurnal Agroekoteknologi, 2016)
ABSTRACT The use of black soybean is still very little compared to yellow soybeans are widely used as raw material for food. The low production of soybean Indonesia one of them because there is not maximal knowledge of farmers in the use of technologies that support sustainable agricultural. Using improved varieties and availability of organic materials is the main requirement to increase soybean production. The objective of the research is to determine the variety and type of organic material on the growth and production of black soybeans.The experiment was conducted in Setia Budi Street, Simpang Pemda District of Medan Selayang on December 2015 to March 2016, using a factorial randomized block design with three factors, the first factor is varieties (Cikuray, Detam-2, Malikka) and the second factor is organic matter (Kontrol, Kompos Jerami Padi, Biochar, Bokashi). Observed were plant height, root dry weight, seeds per plant dry weight, dry weight of seeds per plots, the dry weight of 100 seeds, dry weight of seeds per hactare.The results showed that application of varieties increased plant height 4 and 6, dry weight of seeds per plots. The dry weight of 100 seeds, dry weight of seeds per hactare and organic matter increasing the seeds per plant dry weight, dry weight of seeds per plots and dry weight of 100 seeds. Keywords: black soybean, organic matter, varieties  ABSTRAK Penggunaan kedelai hitam masih sangat sedikit dibandingkan kedelai kuning yang banyak digunakan sebagai bahan baku pangan. Produktivitas tanaman kedelai nasional mengalami penurunan setiap tahunnya. Rendahnya produksi kedelai Indonesia salah satunya dikarenakan belum maksimalnya pengetahuan petani dalam penggunaan teknologi produksi yang mendukung pertanian berkelanjutan. Menggunakan varietas unggul dan tersedianya bahan organik merupakan syarat utama dalam meningkatkan produksi kedelai. Tujuan penelitian yakni untuk mengetahui varietas dan jenis bahan organik terhadap pertumbuhan dan produksi   kedelai hitam. Penelitian dilaksanakan di Jalan Setia Budi, Simpang Pemda Kecamatan Medan Selayang pada Desember 2015 sampai Maret 2016, menggunakan Rancangan Acak Kelompok Faktorial dengan dua faktor yaitu Varietas (Cikuray, Detam-2, Malikka) dan Bahan Organik (Kontrol, Kompos Jerami Padi, Biochar, Bokashi). Peubah yang diamati adalah tinggi tanaman, bobot kering biji per tanaman, bobot kering biji per plot, bobot 100 biji kering, bobot kering biji per hektar. Hasil penelitian varietas meningkatkan Tinggi tanaman 4 dan 6 MST, bobot kering biji per plot, bobot 100 biji, dan bobot kering biji/ha. Pemberian pemberian bahan organik meningkatkan bobot kering biji per tanaman, bobot kering biji per plot, dan bobot kering biji/ha. Kata kunci : bahan organik, kedelai hitam, varietas